Analisa Kebijakan PAI di Indonesia (Dampak UU Nomor 14 Tahun 2005 Tentang Guru dan Dosen Bagi Guru Madrasah) - Sunarto, Sunarto (Universitas Islam Negeri Raden Intan Lampung, 2015)
Law No. 14 The year 2005 on Teachers and Lecturers stated that. Teachers are professional educators with the primary task of educating, teaching, guiding, directing, train, assess, and evaluate students in early childhood education, formal education, primary education and secondary education. Professional teachers should have academic qualifications, competence, teaching certificate, physically and mentally healthy, and have the ability to achieve national education goals.This requires the setting of the position of teachers and lecturers as professionals, It should also be noted the efforts to maximize the function and the strategic role of teachers and lecturers who uphold the rights and obligations of teachers and lecturers as professionals, coaching and professional development of teachers and lecturers, legal protection, the protection of the profession, as well as workplace health and safety Perlindungan. Thus was born the law no. 14 of 2005 on teachers and lecturers. In connection with it in this paper will discuss the analysis of the impact of law no. 14 of 2005 on teachers and lecturers for madrassa teachers.